Analysis the oral tradition adi-adi structure of the daya society - Fitri Ariana; Missriani Missriani; Arif Ardiansyah (Journal of Educational and Learning Studies, 2021)
The background of this research is that Adi-adi art is one of the oral traditions of the Daya tribe that needs attention. This study aims to analyze the structure of Adi-adi's text. Data collection using ethnographic methods and literature study. Data analysis using structural methods. The instrument in this study was the researcher himself using field notes and records. The findings in this study include: Adi-adi's text structure consists of stanzas, lines, rhymes, and contents. The main function of Adi-adi's performance which is the data in this study is as entertainment. It can be concluded that Adi-adi has the same structure as poem and Adi-adi still has a function for the Daya tribe community. Analysis of language and the process of creation in Adi-Adi can be the object of study for future researchers.